Pelvic Floor Reabilitation in Complete Spinal Cord Injury - Fizzotti, Gabriella (British Journal of Healthcare and Medical Research, 2023)
Introduction: One of the most relevant disabilities is caused by spinal cord injury (SCI). Typical causes of spinal cord damage are trauma, disease, or congenital disorders SCI compromises the function of central nervous system.t. The pelvic floor represents the lower closure of the pelvis and it is able to support the pelvic organs. Case Report: acute SCI patient, following intradural-extramedullary spinal neoformation level D6-D9. Rehabilitation approach to pelvic floor included a series of techniques aimed at improving the contractility and tone of the pelvic floor muscles. At the end of 6 sessions patient presented major awareness of bladder emptying through intermittent catheterization and the partial recovery of tactile sensitivity in the wall of the vagina. Conclusions: This paper suggest the possibility for inserting the treatment of the pelvic floor in the neuro-motor rehabilitation program of the complete SCI. The awareness of pelvic floor muscles contraction and bladder functions represent important goals.